Implementation of the Hazard and Operability Study (HAZOPS) Method in the Sedimentation Unit of the Gas Industry Wastewater Treatment Plant: Implementasi Metode Hazard and Operability Study (HAZOPS) di Unit Pengendapan Instalasi Pengolahan Air Limbah Industri Gas - Novitrie, Nora Amelia (Journal of Research and Technology, 2023)
The gas industry generally uses TEG (Triethylene Glycol) to extract the water content in natural gas. TEG that has been used can be reused by means of regeneration. . This process has a side product, namely water vapor. The water vapor produced from the regeneration process can be used for sanitation purposes by changing the phase to liquid (water). Water produced from regeneration must go through the stages of wastewater treatment before being used because it contains impurities. One of the stages of wastewater treatment is settling which includes flocculation and coagulation. The sedimentation process is one of the sources of danger in wastewater treatment. Sources of danger in the deposition process can come from added chemicals, mixing processes that occur due to reactions between chemicals and the use of agitators which, if not appropriate, can cause process failure or danger to workers. Hazard identification techniques are needed in the deposition process to prevent process failures or work accidents. In this research, hazard identification was carried out using HAZOPs. The risk assessment of the settling unit in the gas industry wastewater treatment plant shows that there are 2 medium risks and 2 low risks